Upregulation of miR-216a-5p by Lentinan Targeted Inhibition of JAK2/STAT3 Signaling Pathway to Reduce Lung Adenocarcinoma Cell Stemness, Promote Apoptosis, and Slow Down the Lung Adenocarcinoma Mechanisms - Chen, Quan; Zheng, Yiming; Chen, Xia; Ge, Pengfei; Wang, Pengcheng; Wu, Bingbing (Frontiers in Oncology, 2021)
To investigate the effect of Lentinan (LNT) on lung adenocarcinoma (LUAD) cell stemness and its mechanism. In this study, we founded that LNT significantly reduce the cell proliferation, activity, migration, invasion, and stemness of LUAD cells, and promote their apoptosis compared with the control group in vitro. Moreover, LNT significantly inhibited the volume and weight of tumors of nude mice in vivo. At the same time, LNT can significantly up-regulate miR-216a-5p levels and reduce the protein expression of phospho-JAK2 (Y1007/1008) and phospho-STAT3 (Tyr705), thereby inhibiting the JAK2/STAT3 signaling pathway. Interfering with miR-216a-5p expression and activating the JAK2/STAT3 signaling pathway can significantly reverse LNT inhibitory effects on LUAD. Collectively, LNT can inhibit the JAK2/STAT3 signaling pathway by up-regulating miR-216a-5p, reducing stemness, and promoting LUAD cells apoptosis, then slow down LUAD occurrence and development, providing concepts and experimental foundation treating patients with LUAD.